Digital Regulatory Communication And Youth Participation In Indonesia’s Digital Economy - Gusty, Ryndian; Siregar, Ira Nur Dewita; Syahlina, Maya; Hasibuan, Ervina Rosarina; Purba, Ade Rasinta Herli Kristiani (Universitas Riau, 2025)
This study investigates the intersection between digital regulatory communication and youth participation in Indonesia’s evolving digital economy. As the nation approaches its demographic bonus era (2030–2040), young people have become key drivers of digital innovation, entrepreneurship, and creative economy growth. However, their potential remains constrained by a regulatory environment that is fragmented, reactive, and inadequately adaptive to the dynamic nature of digital transformation. Using a qualitative juridical-normative and conceptual approach, this research critically analyzes the alignment between existing legal frameworks—such as the Electronic Information and Transactions Law, the Youth Law, the Job Creation Law, and the Creative Economy Regulation—and the practical realities of youth-driven digital innovation. Findings reveal a persistent structural gap between regulatory intentions and implementation, marked by legal ambiguity, administrative rigidity, and limited youth participation in policymaking processes. These conditions weaken institutional trust and hinder the inclusiveness of Indonesia’s digital transformation agenda. The study identifies that the dominance of control-oriented regulation (rule-based approach) often restricts innovation freedom, while the absence of adaptive mechanisms—such as regulatory sandboxes and co-regulation frameworks—reduces opportunities for legal experimentation and creative growth among young innovators. This research contributes theoretically by integrating youth empowerment theory, digital governance theory, and socio-legal perspectives to conceptualize adaptive digital regulation as a facilitative rather than restrictive instrument. Practically, it proposes a participatory regulatory communication model emphasizing inclusivity, policy harmonization, and digital legal literacy as prerequisites for sustainable youth engagement. The study concludes that achieving Indonesia’s “Golden Vision 2045” requires a shift from security-oriented to empowerment-based regulation—where law functions not merely as control, but as a communicative, enabling, and transformative medium for youth-led digital innovation.